Women’s Perception on the Relevance of Midwife-Led Continuity of Care in Selected Facilities in Rivers State, Nigeria: Mixed-Methods Study - Patience Ibe; Eunice Osuala; Samuel Onuoha; Chinemerem Eleke (IPS Journal of Basic and Clinical Medicine, 2026)
Midwife-led continuity of care (MLCC) is globally recognized for improving maternal health outcomes through consistent, personalized care. In Rivers State, Nigeria, women's perceptions on the MLCC is poorly documented. This study evaluated the perceived relevance of MLCC in meeting maternity care needs among women obtaining maternity services in selected primary health facilities in Rivers State, Nigeria. A parallel convergent mixed-methods design was employed. The study was conducted in four randomly selected primary healthcare centres: Orogbum, Ozuoba, Aluu, and Omoku. The study sample comprised 14 purposively selected informants for the qualitative phase and a conveniently selected 292 respondents for the quantitative phase. Face-to-face interviews were conducted, transcribed, and analysed thematically for the qualitative phase. For the quantitative phase, data were collected via structured questionnaires and analysed using SPSS 25 software. Descriptive statistics summarized participants’ characteristics, while Chi-square analysis (p < 0.05) tested associations between variables. Quantitative results showed a favourable overall perception (grand mean = 2.80), with strong agreement that continuity with the same midwife improves trust, communication, informed decision-making, and maternal emotional well-being. Chi-square analysis demonstrated a significant association between parity and perception of MLCC (p < 0.001), with primiparous and multiparous women reporting more positive perceptions than grand multiparous women. Qualitative findings further showed that continuity of care enhances confidence, strengthens therapeutic relationships, and provides emotional security, although concerns were raised about feasibility in understaffed facilities. Health systems should strengthen the implementation of MLCC through improved staffing, supportive policies, and integration into primary maternal services.